Chemical Characterization of a Volatile Dubnium Compound, DbOCl3. Issue 33 (2nd July 2021) - Chiera, Nadine M.; Sato, Tetsuya K.; Eichler, Robert; Tomitsuka, Tomohiro; Asai, Masato; Adachi, Sadia; Dressler, Rugard; Hirose, Kentaro; Inoue, Hiroki; Ito, Yuta; Kashihara, Ayuna; Makii, Hiroyuki; et al.
Abstract: The formation and the chemical characterization of single atoms of dubnium (Db, element 105), in the form of its volatile oxychloride, was investigated using the on‐line gas phase chromatography technique, in the temperature range 350–600 °C. Under the exactly same chemical conditions, comparative studies with the lighter homologues of Group 5 in the Periodic Table clearly indicate the volatility sequence being NbOCl3 > TaOCl3 ≥ DbOCl3 . From the obtained experimental results, thermochemical data for DbOCl3 were derived. The present study delivers reliable experimental information for theoretical calculations on chemical properties of transactinides. Abstract : Dubnium obeys Mendeleev's periodicity. Fifty years after the discovery of this element, its chemical behavior was experimentally revisited. From the gas chromatographic investigation of the volatile oxychloride compound, a trend of decreasing volatility along Group 5 elements was deduced, in agreement with the expectations by the laws established in the Periodic Table.